Pocket Guide to Malignant Melanoma. - Buchan, John (John Wiley & Sons, 2007)
The ability to diagnose melanomas and ensure that they are properly and swiftly treated can save lives. The latter part of this century has witnessed a rise in the incidence of this life-threatening form of skin cancer, which is linked to sun exposure. Public health campaigns have begun to raise awareness of the problem and people are now seeking medical advice about pigmented lesions. The reader is guided through the diagnosis and differential diagnosis with the aid of full color photographs, and there is a guide to interpreting the pathology report.